A red pumpkin seed extract reduces melanosome transfer to keratinocytes by activation of Nrf2 signaling. (25th July 2018) - Endo, Karin; Mizutani, Taeko; Okano, Yuri; Masaki, Hitoshi
Summary: Background: The induction of skin pigmentation by ultraviolet (UV) radiation has been shown to result from factors secreted from UV‐exposed keratinocytes that enhance melanogenesis in melanosomes (MSs) and stimulates their transfer to keratinocytes. Among those factors, it has been reported that α‐melanocyte stimulating hormone, which is converted from the precursor proopiomelanocortin (POMC) following UV exposure, stimulates the transfer of MSs from melanocytes to surrounding keratinocytes. Objective: The purpose of this study was to evaluate the effects of a red pumpkin seed (RPS) extract on the transfer of MSs to keratinocytes and to clarify the involvement of reactive oxygen species (ROS) on the UVB‐induced transfer of MSs. Methods: The transfer of MSs into keratinocytes was examined by measuring the incorporation of fluorescent beads, which were used as pseudo‐MSs. mRNA expression levels of POMC, Nrf2, and Nrf2‐related genes were determined using real‐time PCR. Intracellular ROS levels were estimated with H2 DCFDA. Results: The incorporation of fluorescent beads into keratinocytes was enhanced by treatment with the conditioned medium (CM) from keratinocytes exposed to UVB or H2 O2 . UVB or H2 O2 exposed keratinocytes had an up‐regulated mRNA expression level of POMC. Treatment of keratinocytes with the RPS extract enhanced their intracellular antioxidant system via the activation of Nrf2 signaling and suppressed their incorporation of fluorescent beads that had been stimulated by the CM from UVB or H2 O2 exposed keratinocytes. Conclusion: These results indicate that the RPS extract suppresses MS transfer stimulated by ROS generated following UVB exposure through the activation of Nrf2 signaling.